Minimal Residual Disease in Melanoma:molecular characterization of in transit cutaneous metastases and Circulating Melanoma Cells recognizes an expression panel potentially related to disease progression. (2020) - Rapanotti, Maria Cristina; Viguria, Tara Mayte Suarez; Spallone, Giulia; Terrinoni, Alessandro; Rossi, Piero; Costanza, Gaetana; Campione, Elena; Lombardo, Paolo; Pathirannehalage, Cristine Don; Orlandi, Augusto; Bernardini, Sergio; Bianchi, Luca
Highlights: MCAM/MUC18/CD146 and/or ABCB5 as melanoma-specific-targets are effective in the selection of highly primitive Circulating Melanoma Cells (CMCs), highly aggressive and able to metastasize. Assessment of a robust selected biomarker qualitative expression panel contemplating angiogenic-potential, melanoma-initiating and melanoma-differentiation drivers, cell-cell adhesion molecules and matrix-metalloproteinases, was performed on cutaneous in transit metastases and on the three enriched distinct CMC sub-populations. Definition of those genes, particularly MCAM/MUC18/CD146, MMPs and VE-Cadh associated to disease progression and able to recognize melanoma high-risk or low-risk disease patients. Longitudinal monitoring, documented shutdown of all gene-expressions in all three CMC subsets, whilst persistency or acquisition of MCAM/MUC18/CD146, VE-CADH and MMPs was documented in disease progressive cases, highlighting those genes associated with disease spreading progression and minimal residual disease. Abstract: Isolating circulating melanoma cells (CMCs) represents a powerful method to monitor minimal residual disease. We documented that MCAM/MUC18/CD146 expression is strongly associated with disease progression. ABCB5 is melanoma-stem antigen with self-renewal, proliferation, differentiation, tumorigenicity capabilities. These findings supported us to improve CMC detection, investigating MCAM/MUC18/CD146 and ABCB5 as enrichment targets in MM progression. Moreover, we decided to compare possible molecular diversity of these CMC fractions with metastatic tissue expression, collecting concomitantly cutaneous in transit metastases (CTM). We enriched CMCs from eight melanoma patients staged ≥pT1b AJCC, who developed CTMs at baseline or during follow up. We assessed a gene expression panel comprising ABCB5, the differentiation markers ( Tyrosinase, MART1 ), angiogenic factors ( VEGF, bFGF ), the cell-cell adhesion molecules ( MCAM/MUC18/CD146 5′-portion, Long, and Short isoforms, E-Cadherin, N-Cadherin, VE–Cadherin ) and matrix-metallo-proteinases ( MMP2 and MMP9 ) via high-sensitive RT-PCR. Preliminary findings defined three distinct sub-populations: "endothelial" CD45-CD146+CMCs, "stem" CD45-ABCB5+CMCs and a "hybrid- stem-endothelial"- CD45-MCAM+ABCB5+CMCs. The expression panel documented that – almost high expression found in CTMs – like in 73.5% of CMCs resulted positive for at least one transcript at baseline, showing gene-expression variability. Longitudinal monitoring documented shut-down of all gene-expressions in "endothelial"- and "hybrid stem-endothelial"-subsets, whilst persistency or acquisition of MCAM/MUC18/CD146, VE-CADH and MMPs was documented in disease-progression status. Conversely, a drastic expression shut-down was documented when patients achieved clinical remission. The "stem"- CMCs fraction" showed quite lower gene expression frequencies. MCAM/MUC18/CD146 and ABCB5 as melanoma-specific-targets are effective in the selection of highly primitive CMCs and highlights those putative genes associated with disease spreading progression.